A comparative review of CET4 essay writing assessments with insights from the CEFR level descriptors - Li, Changlin; Nik Aloesnita, Nik Mohd Alwi; Mohammad Musab, Azmat Ali (Zes Rokman Resources, 2025)
The comparative analysis of essay writing assessment criteria, particularly the Common European Framework of Reference for Languages (CEFR) and the College English Test Band 4 (CET4), has attracted growing attention in language testing research. Building upon previous research from the past decade, this study examines the comparison between CET4 writing rubrics and CEFR level descriptors, with a particular focus on the influence of task complexity under the CEFR level descriptors. Underpinned by Robinson’s Cognition Hypothesis (CH) and Skehan’s Limited Attentional Capacity Model (LACM), this study explores how variations in task complexity impact linguistic outcomes in CET4 essay writing. Robinson’s CH suggests increased task complexity promotes greater lexical and syntactic complexity, whereas Skehan’s LACM emphasises the trade-offs between accuracy, fluency, and complexity under cognitive constraints. Over the past decade, research has applied the theoretical models to assess task complexity dimensions, specifically “+/- planning time (PT)” and “+/- few elements (FE)” in CET4 essay writing. Empirical findings have demonstrated significant correlations between task complexity and CEFR-aligned performance indicators. Accordingly, this study conducts a comprehensive review of the relationship between CET4 writing rubrics and CEFR level descriptors, identifying points of convergence and divergence in writing criteria. Findings suggest that integrating the CEFR into CET4 assessment practices enhances comprehensiveness, supporting more specific evaluation dimensions for essay writing. Overall, this study provides insights into writing assessment practices by integrating theoretical perspectives and recent empirical evidence. The findings hold implications for educators, particularly in bridging the CET4 and CEFR writing assessment and enhancing task-based essay writing instruction.